1994
DOI: 10.1128/jb.176.20.6229-6237.1994
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of bacitracin resistance in gram-negative bacteria that synthesize exopolysaccharides

Abstract: Four representative species from three genera of gram-negative bacteria that secrete exopolysaccharides acquired resistance to the antibiotic bacitracin by stopping synthesis of the exopolysaccharide. Xanthomonas campestris, Sphingomonas strains S-88 and NW11, and Escherichia coli K-12 secrete xanthan gum, sphingans S-88 and NW11, and colanic acid, respectively. The gumD gene in X. campestris is required to attach glucose-P to C55-isoprenyl phosphate, the first step in the assembly of xanthan. A recombinant pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
58
0
1

Year Published

1996
1996
2024
2024

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(59 citation statements)
references
References 36 publications
(28 reference statements)
0
58
0
1
Order By: Relevance
“…The order of assembly prior to polymerization is glucose, glucose, mannose, glucuronic acid, and finally mannose (24). Our genetic complementation tests also showed that the wild-type gumD gene of X. campestris could restore synthesis of sphingans in analogous Bac r Sps Ϫ (sphingan polysaccharide-negative) mutants of Sphingomonas strains (45). Since there are two glucose residues in the backbone of each of the sphingans, we reasoned that the Bac r Sps Ϫ mutants were probably also blocked in the transfer of glucose-P to IP.…”
mentioning
confidence: 57%
See 1 more Smart Citation
“…The order of assembly prior to polymerization is glucose, glucose, mannose, glucuronic acid, and finally mannose (24). Our genetic complementation tests also showed that the wild-type gumD gene of X. campestris could restore synthesis of sphingans in analogous Bac r Sps Ϫ (sphingan polysaccharide-negative) mutants of Sphingomonas strains (45). Since there are two glucose residues in the backbone of each of the sphingans, we reasoned that the Bac r Sps Ϫ mutants were probably also blocked in the transfer of glucose-P to IP.…”
mentioning
confidence: 57%
“…Most of the gum genes required by this bacterium for synthesis and secretion of xanthan gum have been described (3,6,19,20,58). Previously we learned from genetic complementation tests that a special class of mutations in X. campestris which are simultaneously xanthan gum negative (Gum Ϫ ) and resistant to bacitracin (Bac r ) are in the gumD gene (45). This gene is required to transfer glucose-P from UDP-Glc to a carrier isoprenylphosphate (IP) to give glucoseisoprenylpyrophosphate (Glc-PPI) and is the first dedicated step in synthesis of xanthan gum (59).…”
mentioning
confidence: 99%
“…BacA homologs were also identified in Streptococcus pneumoniae and Staphylococcus aureus and are important for resistance to bacitracin, presumably by increasing the synthesis of C 55 -isoprenyl phosphate (6). In some gramnegative bacteria, mutations that block the synthesis of exopolysaccharides also lead to bacitracin resistance, presumably by increasing the supply of the common C 55 -isoprenyl phosphate carrier (22).…”
mentioning
confidence: 99%
“…A. pullulans strain NRRL Y-2331-1, which produces high yields of a nonpigmented form of pullulan, 9 was obtained from the United States Department of Agriculture (USDA). The growth media consisted of a complex nitrogen stock solution with sucrose as the carbon source, 5 containing (per 1 L of ultrapure water): 2.0 g of yeast extract, 0.5 g of (NH 4 ) 2 SO 4 , 1.0 g of NaCl, 0.2 g of MgSO 4 , 3.0 g of K 2 HPO 4 , 0.01 g of FeSO 4 , 0.01 g of MnSO 4 , 0.01 g of ZnSO 4 , and 50 g of sucrose. All ingredients, excluding ZnSO 4 , MnSO 4 , FeSO 4 , and MgSO 4 , were mixed and autoclaved for 45 min at 121°C.…”
Section: Methodsmentioning
confidence: 99%
“…2 However, naturally occurring and mutant strains of A. pullulans exist that produce reduced levels of melanin. 5,6 A. pullulans may produce other macromolecules, depending on culture conditions. For example, cells grown on sucrose produce pullulan and an acidic glucan with uronic acid components, whereas cells cultured on maltose produce a heteropolysaccharide containing glucose, galactose, and mannose.…”
Section: Introductionmentioning
confidence: 99%